PENGARUH PENERAPAN MODEL PEMBELAJARAN TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 28 PADANG TAHUN PELAJARAN 2013/2014 - Darwati, Elmi; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2013)
This research was conducted based on the fact that the studentsâ understanding on mathematics concept was still low and they seemed unable to answer questions delivered by the teacher. This research was aimed at revealing whether the use of Talking Stick learning model could improve the second year studentsâ understanding on mathematics concept better than that of conventional learning at SMPN 28 Padang. This was an experimental research which used random research design toward the subject. The data gathered was analyzed by using t-test. The result of data analysis indicated that the two classes were normally distributed and homogeny (Î±=0.05). The result of hypothesis test by using MINITAB showed that P-Value was 0.005 signifying that hypothesis was accepted. Thus, it was concluded that the use of Talking Stick learning model could improve the second year studentsâ understanding on mathematics concept better than that of conventional learning model at SMPN 28 Padang in Academic Year 2013/2014 with 95% of reliable level.